TINJAUAN YURIDIS PERLINDUNGAN HUKUM TERHADAP BADAN HUKUM KOPERASI SIMPAN PINJAM TERHADAP DEBITUR WANPRESTTASI: Studi di Koperasi Simpan Pinjam Sejahtera Mataram - Ni Made Aryani Saraswati Dewi; H. Djumardin Djumardin (Private Law, 2023)
This study aims to find out the factors causing debtors to default and to understand the form of protection of legal entities of savings and loan cooperatives, as well as the form of settlement carried out by the Sejahtera Savings and Loan Cooperative if the debtor is in default. Based on the results of this study, it can finally be concluded that the causes of debtors defaulting on the Sejahtera Savings and Loan Cooperative are internal factors, external factors, and the incomparable value of collateral. The form of legal protection for savings and loan cooperatives if the debtor defaults is through Standard Operating Management, Task Force Team, and the form of agreement that has been agreed upon by the cooperative and members through the goods or collateral of the debtor given to the cooperative. The form of settlement is in two ways: non-litigation and litigation; by deliberation or kinship; andthe last is the criminal or legal path.